2018
DOI: 10.1590/s0100-204x2018000200011
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of cactus pear cladodes under different fertilization and harvesting managements

Abstract: The objective of this work was to evaluate the effects of combined phosphorus and nitrogen fertilization and of harvesting frequency on the chemical composition of 'Gigante' cactus pear (Opuntia ficus-indica) cladodes. The experiment was carried out in two municipalities, Quixadá and Tejuçuoca, in the state of Ceará, Brazil. Fertilization with nitrogen (urea) and phosphorus (single superphosphate) was done with nine doses, respectively: 10 and 70, 70 and 10, 70 and 70, 70 and 130, 100 and 100, 130 and 70, 130 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
(23 reference statements)
0
4
0
2
Order By: Relevance
“…Pessoa et al (2020) observed cactus NDF (268 g kg -1 DM) similar to the ones observed in the current research for 'IPA-20'. In contrast, Gomes et al (2018) observed average values of 294 g NDF/kg DM for Opuntia ficus-indica Mill at one year of growth. Regardless of cactus species, first-order cladodes presented greater NDF values.…”
Section: Chemical Compositionmentioning
confidence: 72%
“…Pessoa et al (2020) observed cactus NDF (268 g kg -1 DM) similar to the ones observed in the current research for 'IPA-20'. In contrast, Gomes et al (2018) observed average values of 294 g NDF/kg DM for Opuntia ficus-indica Mill at one year of growth. Regardless of cactus species, first-order cladodes presented greater NDF values.…”
Section: Chemical Compositionmentioning
confidence: 72%
“…Less frequent harvesting of forage cactus leads to greater biomass productivity [18], and, consequently, the extraction of nutrients from the soil tends to be higher. Greater biomass productivity with less frequent harvests contribute to the development of plants that are taller and wider, with greater quantity, length, width, and thickness of cladodes, characteristics that reflect higher yields and changes in the chemical composition of forage cactus [47]. Cactus typically has a higher cladode area index (CAI) with biennial frequency when compared to plants harvested annually, and that helps to improve primary productivity [48].…”
Section: Discussionmentioning
confidence: 99%
“…Semiarid regions, high evapotranspiration is a limiting factor for plant biomass production (Gomes et al, 2018). Even with water for irrigation, the use of more adapted genotypes is an indispensable condition for the best use of this resource, so that the use of a minimum irrigation depth to maintain the forage crop may be a relevant alternative in view of a possible water limitation due to climatic factors.…”
Section: Inmentioning
confidence: 99%